2021
DOI: 10.1002/fee.2296
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling carbon‐cycle processes from ecosystem to global scales

Abstract: C arbon (C) is the building block of life. Global photosynthesis generates approximately 100 terawatts (TW) of energy each year by converting solar radiation into stored chemical energy (Barber 2009). Photosynthesis also represents the largest global annual C flux, of ~125 petagrams (Pg; where 1 Pg equals 10 15 grams [g] and 1 Pg C is roughly equivalent to 0.47 parts per million [ppm] of CO 2), with the second greatest flux consisting of the subsequent release of CO 2 via respiration (~122 Pg C/year). Both of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Fei et al (2018), for instance, demonstrated that the biodiversity-productivity relationship changes across a large spatial extent, with climatic variation as the underlying determinant, while Read et al (2018) used continental-scale monitoring of small mammal populations to demonstrate how trait space can explain increased diversity at lower latitudes. Macrosystems biology is also poised to test other long-standing hypotheses, such as scaling interactions across the regional and global biosphere (see Ballantyne et al 2021). Contemporary tools (eg national and independent sensor networks, remote sensing, citizen-science programs) provide new opportunities for assessing previously untestable concepts and hypotheses.…”
Section: General Characteristics Of Macrosystems Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Fei et al (2018), for instance, demonstrated that the biodiversity-productivity relationship changes across a large spatial extent, with climatic variation as the underlying determinant, while Read et al (2018) used continental-scale monitoring of small mammal populations to demonstrate how trait space can explain increased diversity at lower latitudes. Macrosystems biology is also poised to test other long-standing hypotheses, such as scaling interactions across the regional and global biosphere (see Ballantyne et al 2021). Contemporary tools (eg national and independent sensor networks, remote sensing, citizen-science programs) provide new opportunities for assessing previously untestable concepts and hypotheses.…”
Section: General Characteristics Of Macrosystems Researchmentioning
confidence: 99%
“…Macrosystems biology or similar approaches will continue to be relevant to ecological science because small-scale methodologies do not typically upscale readily and therefore fail to adequately capture or describe large-scale spatial patterns. For example, small-scale approaches do not capture properties such as teleconnections (see Tromboni et al 2021), and mesoscale C flux can be difficult to connect to larger scale approaches (see Ballantyne et al 2021). Macrosystems biology offers a distinctive approach that could provide valuable ecological understanding in much the same way that long-term approaches uncovered "ecological surprises" (Dodds et al 2012).…”
Section: The Future Of Macrosystems Biologymentioning
confidence: 99%
See 3 more Smart Citations